Evaluación de tres niveles de sombra sobre parámetros morfo-fisiológicos en plantas de cacao (Theobroma cacao L) clon EETP800 en etapa de crecimiento vegetativo, en la provincia de Zamora Chinchipe, sector El Padmi - Puchaicela Murquincho, Ana Belen (2022)
The cultivation of cacao (Theobroma cacao L.) is very important in Ecuador; it is one of the main export products and one of its economic and social sources, generating important foreign exchange. In this crop there are important environmental factors, such as shading, which influences the development of the crop and has not been considered in different studies despite the fact that this species is considered preferably shade tolerant. Based on the above, the main objective of this study was to evaluate the effect of three levels of shade on cacao (Theobroma cacao L) clone EETP800, which was carried out at the Experimental Station "El Padmi" of the UNL, in the province of Zamora Chinchipe, on a cocoa crop 1 year 8 months old, under a DCA arrangement with 3 treatments (0%, 35% and 80% shade) and 6 replications. Variables such as height, shoot length, crown diameter, trunk cross-sectional area (ASTT), leaf area index (LAI), chlorophyll concentration and stomatal density, soil pH and EC were measured. The results obtained showed that in most of the variables there were no significant differences between treatments. However, the full light treatment allowed taller plants to be obtained, and the 35% shade treatment favored an increase in chlorophyll, A, B, and total chlorophyll. In general, the results of the research show that the use of shade does not show statistically significant effects on physiological variables of clone EETP800, which shows that in this area it would not be necessary to implement shade with saran mesh. Key words: Theobroma cacao L, shade, growth.